THE EARLY KAZANIAN "SOYANA RIVER FLORA": ITS PLACE AMONG COEVAL FLORAS AND IN PHYTOGEOGRAPHIC ZONES OF THE ANGARALAND - Ignat'ev I.A.; Naugol'nykh S.V. (My University, 2001)
The early Kazanian flora of the Soyana River site includes the following plant groups: ruflorians Rufloria sylovaensis (Neub.) comb. Nov.; vojnovskyans Cordaites sp., Crassinervia sp., Lepeophillum sp., Sylvella sp., Jordania sp., Samaropsis spp., and Cordaicarpus sp.; conifers Cyparissidium sp.; dicranopylls Entsovia cf. rarisulcata S. Meyen; small-leaved Zamiopteris ex gr. elongata (Zal.) Neub.; cardiolepidians Phylladoderma sp.; pteridosperms Cardioneura ex gr. vorcutense Zal.; lepidophytes Viatscheslaviophyllum cf. kamiense Esaul.; ferns Pecopteris ex gr. leptophylla Bunb. and Lobatopteris sp.; articulates Annularia aff. carinata Gutb. Regional Kazanian floras and reconstructed phytogeographic zones of the Angaraland are considered. The extreme northern part of the Angaraland presumably corresponded to a narrow tundra zone with cold climate. The boreal zone with moderately cold, predominantly humid climate occupied the greater part of the land that was covered with forest massifs ("cordaitean taiga"). Southwestern areas of the Angaraland (cis-Urals and northern part of the Russian platform) represented the subboreal zone of moderately warm climate that hosted plant formations of several types, among them the deciduous cordaitean and cardiolepidian forests, which grew within present-day areas of the cis-Urals and Pechora basin. Westward of the Angaraland, the subboreal zone is traceable in the Arctic North America. The early Kazanian "Soyana River flora" presumably represented an island plant formation of the subboreal zone. Ferns and articulates occurring in this flora are characterized.
Keywords: Kazanian; Permian; Soyana River; Paleozoic::Permian; Палеозой::Пермская